A Case of High Power Distance: Sycophantic Adherence in Fraudulent Malfeasance and its Critical Implications for Auditor Oversight - Ach Maulidi (Australasian Accounting, Business and Finance Journal, 2024)
The objective of this study is to observe the dynamics of romantic relationships between leaders and subordinates in the context of committing fraud. We conducted semi-structured interviews with participants from the upper echelons of Indonesia’s local government. These individuals were chosen due to their roles in overseeing the organization’s financial resources. Our findings indicate that obedience to authority serves as an alternative explanation for fraudulent activities. Subordinates frequently justify their fraudulent actions as part of their organizational duties. The presence of romantic relationships between leaders and subordinates facilitates manipulative activities and makes fraudulent behavior more feasible. Consequently, when such romantic relationships are present, collusive fraud is more likely to occur. Our research extends beyond traditional frameworks like the fraud triangle, fraud diamond, and fraud pentagon. Therefore, we offer recommendations for organizations to develop alternative strategies for fraud mitigation.
Keywords: Obedience to authority; Fraud Triangle; Romantic Relationships; Corrupt Leader; Subordinates